Effect of tray drying temperature and drying time on properties of cricket powder - Lida Simasatitkul; Kittisak Thongprom; Thunyapisit Jaroensang; Karittha Im-orb (E3S Web of Conferences, 2025)
This research studied the production of cricket powder via tray drying and powdering processes by investigating the effect of drying temperature of 80, 90, 100oC and drying time ranging of 30 - 240 min on the properties of cricket powder. The drying rate increased while the moisture content decreased as drying temperature and drying time increased causing it easy to be ground and had good solubility. The cricket powder had dark brown color and its lightness decreased with increasing drying temperature. The produced cricket powder could reach equilibrium moisture content of approximately 5% and the water activity was decreased with increasing drying temperature. Regarding the nutrient content, the change in drying temperature in a range of 80-100oC had no significant effect on the nutrient content. The suitable drying condition of crickets offering the highest protein content of 70.35% was achieved at drying temperature of 80oC and drying time of 240 min. At this condition, 55.57% yield of cricket powder satisfying dry food specification (moisture content of 5.32% and aw of 0.3539) was obtained.
Keywords: Insect Utilization and Effects; Bee Products Chemical Analysis; Microencapsulation and Drying Processes